Collaborative Governance in Addressing Stunting in Tidore Kepulauan City - Saiful Salim; Umanto Umanto (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
Stunting is not only a health issue, but is also closely related to economic, educational, political, and cultural aspects, thus requiring a specific and sensitive cross-sectoral intervention approach. Based on data from the World Health Organization (WHO), Indonesia is one of 17 countries with a double burden of malnutrition and ranks third with the highest prevalence in Southeast Asia, at 36.4%, after Timor Leste (50.5%) and India (38.4%). The distribution of stunting cases tends to be high in areas with high poverty rates and limited access, such as Tidore Kepulauan City, which has been designated as a priority for stunting prevention for the 2018–2022 period. However, through collaborative efforts, the Tidore Kepulauan City Government has succeeded in reducing the stunting rate from 21.3% (2023) to 16.6% in 2024. This study uses a post-positivist approach with qualitative methods to analyze collaborative governance that can reduce stunting amid geographical and economic challenges. The results of this study show: 1) The initial conditions were influenced by human resource inequality, limited access, and sectoral egoism that hampered handling. This evaluation encourages collective action through face-to-face dialogue, data sharing, participatory planning, and joint decision-making; 2) Factors supporting the collaboration process lie in the establishment of clear regulations and information transparency mechanisms, while facilitative leadership plays a role in driving participation, maintaining group dynamics, expanding networks, and empowering communities. Efforts such as the Stunting Forum, family assistance, and Foster Family socialization are key components. These results prove that structured, collaboration-based cross-sector cooperation can be an effective way to overcome stunting in remote and island areas